A Case Report: Intracerebral and Intraventricular Hemorrhage Due to Rupture of Aneurysm in the Middle Cerebral Artery - Siti Setya Sari Aglen; Lidia Chara Tania Ginting; Hendra Irawan (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Intracerebral hemorrhage (ICH) and intraventricular hemorrhage (IVH) caused by aneurysm rupture without subarachnoid hemorrhage (SAH) is a rare condition, with a prevalence of 1.6%. Case: A 40-year-old male presented with a sudden headache, vomiting, and generalized seizures lasting one day. Initially conscious, he later developed recurrent seizures and transient decreased consciousness. He had a history of smoking and uncontrolled hypertension. Neurological examination showed normal motor function and positive neck stiffness. Head CT revealed ICH and IVH without SAH. The patient underwent ventriculoperitoneal (VP) shunt placement. Six months later, follow-up CT showed a hyperdense lesion in the inferolateral right frontal lobe. Digital subtraction angiography (DSA) identified a saccular aneurysm in the right middle cerebral artery (MCA), M1 segment. Endovascular coiling was performed. Discussion: The patient’s symptoms resembled SAHs, including thunderclap headache, vomiting, and decreased consciousness. However, initial CT showed only ICH and IVH without SAH, possibly due to the timing of imaging. Secondary ICH and IVH can result from aneurysm rupture and parenchymal hemorrhage near the ventricles. Seizures may contribute to aneurysm rupture and consciousness loss. Risk factors such as hypertension, smoking, and age were present. DSA confirmed the aneurysm as the bleeding source. Endovascular coiling was done to prevent rebleeding. Conclusion: Prompt diagnosis using CT and DSA is critical to identify aneurysm-related hemorrhage and guide effective treatment, improving patient outcomes.